Kuwaiti engineers' perspectives of the engineering senior design (capstone) course as related to their professional experiences - AlSagheer, Abdullah, author; Quick, Donald Gene, advisor; Anderson, Sharon K., committee member; Banning, James H., committee member; Malaiya, Yashwant K., committee member (Colorado State University. Libraries, 2010)
This study looks into transfer of learning and its application in the actual employment of engineering students after graduation. At Kuwait University, a capstone course is being offered that aims to ensure that students amalgamate all kinds of engineering skills to apply to their work. Within a basic interpretive, qualitative study-design methodology, I interviewed 12 engineers who have recently experienced the senior design course at Kuwait University and are presently working in industry. From the analysis, four basic themes emerged that further delineate the focus of the entire study. The themes are 1) need for the capstone course, 2) applicability of and problems with the capstone course, 3) industry problems with training, and 4) students' attitudes toward the capstone course. The study concludes that participants are not transferring engineering skills; rather, they are transferring all types of instructions they have been given during their course of study at the university. A frequent statement is that the capstone course should be improved and specifically that it is necessary to improve upon the timing, schedule, teachers' behavior, contents, and format. The study concludes that Kuwaiti engineers on the whole face problems with time management and management support. The study includes some implications for Kuwait University and recommendations that can provide significant support for the development of the Senior Design (Capstone) Course. For examples: the project must be divided into phases to ensure timely completion of deliverables. In order to motivate students for hard work and to achieve true transfer of learning, Kuwait University is required to communicate with certain organizations to place its students at their research centers for capstone projects. All universities, including Kuwait University, should hire faculty specifically to run the capstone course. In conclusion, the study includes some suggestions for further research studies focused on issues related to the Senior Design (Capstone) Course. Future researchers should focus on developing the project-based course in earlier stages of students' educational program by investigating more about the relationship between student achievement and the market demand.
Keywords: Jāmiʻat al-Kuwayt; strategic management; senior design; Kuwait University; engineering education; capstone course; Engineering -- Study and teaching (Higher) -- Kuwait; Learning, Psychology of -- Kuwait; Professional education -- Curricula -- Kuwait; Transfer of training -- Kuwait